Effectiveness of case management and psychological intervention nursing model in bariatric surgery patients - Sun, Qin; Jia, Aimei; Zhang, Yuan; Liang, Dianyuan; Song, Ke; Shari, Norshafarina (Frontiers in Surgery, 2025)
ObjectivesThis study aimed to analyze the significance and value of the case management and psychological intervention model in bariatric surgery patients.MethodsA retrospective study was conducted on 100 patients who underwent bariatric surgery admitted to the Affiliated Hospital of North Sichuan Medical College from January 1, 2021, to December 31, 2023. The patients were divided into two groups based on the nursing model. The control group (n = 50) received conventional nursing, while the experimental group (n = 50) was treated with case management combined with psychological intervention nursing. The changes in physical indicators, patient satisfaction, psychological condition, and quality of life were compared between the two groups.ResultsThe body mass index (BMI) of the experimental group at 12 months post-surgery was significantly different from those of the control group (P < 0.05). Regarding psychological assessment, the anxiety and depression scores of patients showed significant differences at the initial outpatient visit and discharge day (P < 0.05). Quality of life indicators (physical function, bodily pain, emotional function, social function) were statistically significantly different at 6 months post-surgery (P < 0.05).ConclusionThe case management and psychological intervention model can significantly promote weight reduction, psychological assessments, and quality of life functions in patients after bariatric surgery.